2015
DOI: 10.1186/s13071-015-0709-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins associated with pyrethroid resistance by iTRAQ-based quantitative proteomic analysis in Culex pipiens pallens

Abstract: BackgroundMosquito control based on chemical insecticides is considered as an important element in the current global strategies for the control of mosquito-borne diseases. Unfortunately, the development of pyrethroid resistance in important vector mosquito species jeopardizes the effectiveness of insecticide-based mosquito control. To date, the mechanisms of pyrethroid resistance are still unclear. Recent advances in proteomic techniques can facilitate to identify pyrethroid resistance-associated proteins at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 70 publications
3
39
1
1
Order By: Relevance
“…This protein is possibly a cuticular protein as it shows homology to gasp from Drosophila melanogaster, a chitin binding cuticle constituent. Previous research has demonstrated that a down-regulation of some cuticle proteins alongside an up-regulation of others does occur, suggesting that an alteration in cuticle composition may occur, leading to decreased rates of entry of the chemical Wang et al, 2015). However, no cuticle proteins were observed here to be of higher abundance in resistant mites which may indicate that the cuticular changes in resistant mites involve the removal of certain proteins without their replacement.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…This protein is possibly a cuticular protein as it shows homology to gasp from Drosophila melanogaster, a chitin binding cuticle constituent. Previous research has demonstrated that a down-regulation of some cuticle proteins alongside an up-regulation of others does occur, suggesting that an alteration in cuticle composition may occur, leading to decreased rates of entry of the chemical Wang et al, 2015). However, no cuticle proteins were observed here to be of higher abundance in resistant mites which may indicate that the cuticular changes in resistant mites involve the removal of certain proteins without their replacement.…”
Section: Discussionmentioning
confidence: 46%
“…One possible means by which organisms are thought to become resistant is by alteration of the route of entry of the chemical such as a thickening or hardening of the cuticle or other epithelial barriers (Hemingway et al, 2004). A number of cuticular proteins were present in lower amounts in resistant mites (Figure 2(b)), which partly contradicts the trend observed in previous reports (Puinean et al, 2010;Silva, Jander, Samaniego, Ramsey, & Figueroa, 2012;Vontas et al, 2005;Wang et al, 2015). The protein that showed the lowest abundance in the resistant mites, exclusively expressed in the profile of sensitive mites, was a conserved hypothetical protein (Table 3).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…aegypti , C. quinquefasciatus and An. gambiae , but fewer than in D. melanogaster . The phenomenon of many genes physically clustered on the same scaffold was not observed in the An.…”
Section: Resultsmentioning
confidence: 86%
“…Some of the genes affected by clothianidin exposure in our study have also been affected by neonicotinoids or other pesticides in other studies and species. These include muscular genes such as troponin and calponin (Kimura‐Kuroda et al, ; Lewis, Szilagyi, Gehman, Dennis, & Jackson, ; Wang et al, ) and metabolic enzymes such as glucose dehydrogenase (Christen et al, ) and hexosaminidase D (Qi et al, ; Yang, Liu, Liu, Qu, & Qian, ). At a different level, cellular transport genes such as the ABC transport family (Dermauw & Van Leeuwen, ), one member of which was differentially expressed in our study, have been suggested to provide tolerance of neonicotinoids, such as imidacloprid, acetamiprid and thiacloprid, with greater mortality identified for neonicotinoid‐exposed honeybee larvae treated with an ABC inhibitor (Hawthorne & Dively, ).…”
Section: Discussionmentioning
confidence: 99%